EMOTIONAL AND PHYSICAL DISTURBANCES DURING THE CAREGIVING PROCESS BETWEEN FAMILY CAREGIVERS AND STROKE SURVIVORS - Supriadin, Supriadin; Regidor III Dioso; Mohamed Saifulaman Mohamed Said; Datin Hafizah Che Hassan (Journal of Nursing Culture and Technology, 2025)
Background: Stroke is a sudden disruption of blood flow to the brain, causing permanent nerve damage and leading to paralysis. This limits the daily activities of stroke survivors and causes emotional and physical disorders. Family caregivers play a key role in meeting patients' needs but face physical, psychological, social, and financial burdens. To reduce this burden, effective strategies are needed. Caregivers, including family members, friends, or professionals, assist with daily tasks and provide emotional support. Proper caregiving improves the patient's health, reduces disability, and lessens dependence on others. Objective: This literature review aims to identify the emotional and physical disorders faced by family caregivers during the caregiving process of stroke survivors. Method: The research involved selecting articles based on publication year and full-text availability. Relevant studies were chosen from Google Scholar using keywords like "psychosocial support" and "burden on family caregivers of stroke patients form year 2020-2025. The review focused on peer-reviewed articles from the past five years to gather the best evidence regarding psychosocial interventions that alleviate the burden on caregivers.Results: The synthesis of the articles revealed three key interventions to reduce caregiver burden: active rehabilitation through social support, the Information-Motivation-Behavioral (IMB) model, and family stress resilience-based support programs. Conclusion: Family caregivers significantly improve stroke patients' quality of life by helping meet their daily needs, highlighting the importance of effective caregiving in stroke recovery. Keywords: psychosocial support, burden, family caregivers of stroke patients